Gastrointestinal toxicity of gemtuzumab ozogamicin: real-life data from the AMLCG, SAL, and CELL study groups - Knabe, Ricarda; Muller, Philippe; Schliemann, Christoph; Hanoun, Maher; Unglaub, Julia Marie; Weinbergerová, Barbora; Mayer, Jiří; Krekeler, Carolin; Krause, Stefan W.; Kaufmann, Martin; Kraus, Sabrina; Steffen, Björn; et al. (Blood advances, 2025)
TO THE EDITOR:The CD33-directed antibody-drug-conjugate “gemtuzumab ozogamicin” (GO) in combination with the 7+3 standard regimen is currently approved for the treatment of CD33+ acute myeloid leukemia (AML). Although the pivotal ALFA-0701 study did not show a significantly increased toxicity using 7+3 + GO compared with 7+3,1 a slightly higher rate of severe gastrointestinal (GI) toxicity was reported (16% vs 10%), and additional evidence of GO-associated GI toxicity was published.2,3 We observed several cases of severe GI toxicity and therefore analyzed patients treated with GO in a real-world setting.